Study of energy efficiency of pulse hight-speed milling considering the atomic process - Hlushko, Stanislav (National Technical University "Kharkiv Polytechnic Institute", 2025)
The pursuit of reducing energy consumption in metal milling leads to the modernization of mechanisms. These mechanisms utilize the energy released directly during the cutting process. A method for determining energy efficiency in high-speed pulse gear milling is presented, considering atomic level processes. Understanding the physical interactions involved offers new directions for improving the energy efficiency of metal machining.
Keywords: pulse milling; high-speed milling; atomic approach; oscillating milling; metalworking